Stripping on Screen: An Exploration of Female Exploitation in Paul Verhoeven’s Showgirls (1995) - Fletcher, Bethan (2023)
This research explores female exploitation which surrounds Paul Verhoeven’s Showgirls (1995) concerning the film’s pre-production, production, marketing methods, initial critica reception and two distinct revivals. It is proposed that Showgirls is an evolving film which requires continual reassessment in the ever-changing socio-political feminist landscape. The levels of female exploitation present throughout the film’s production history and receptions has developed throughout history as feminist discourse shifts towards the mainstreaming of ‘sex-positive’ third-wave feminism. The film’s pre-production and production are compared to classic sexploitation films in the casting and treatment of young female actresses. Clear links are drawn between sexploitation films with the casting of Berkley and the treatment of Ravera within filming intimate scenes. The advertisement materials and marketing methods hinge on female sexualisation of the film’s actresses which create a potentially exploitative blurring of distinction between the actresses and their characters. The initial critical reception of Showgirls in 1995 carries heavy misogynistic undertones which shame Berkley for her ownership of sexualisation. The camp cult midnight movie revival of Showgirls is dependent on the film’s engagement with female exploitation. Three critical aspects of camp cult midnight movies, camp tones, depictions of failure and transgression are all reliant on female exploitation by the film. The ‘feminist revival’ of Showgirls is proposed as a second-wave revival which celebrates the ‘pro-sex’ fourth-wave feminist attitudes and critiques of female exploitation within media industries found within the film’s narrative. This study updates and expands the sparse academic material concerning Showgirls. Future research should address how developing socio-political climates regarding sex work, stripping and feminism had impacted the film and its receptions. This study provides an in-depth analysis of Showgirls from a feminist perspective attentive to female exploitation in cinema.